Chemical regulation in the Middle East - Wenk, Michael S., 1971- (John Wiley & Sons, 2018)
A noted expert offers a guide to the complex chemical regulations in the Middle East region Chemical Regulation in the Middle East offers an essential guide to the patchwork of chemical regulatory programs and the complex system of permits and licenses that manage chemicals in the countries of the Middle East. The book explores the range of ministry, legislative, and other decrees that encompass pesticides, occupational safety and health, as well as safety data sheets and product labels that address regulation to widely-varying degrees. The author explores the Cooperation Council for the Arab States of the Gulf and reviews the key regulatory agencies and chemical substance regulations. The text outlines the pesticide regulations, occupational safety and health regulations, waste regulations and safety data sheets and labels in Bahrain, Egypt, Israel, Kuwait, Oman, Pakistan, Saudi Arabia, United Arab Emirates and Abu Dhabi. This important guide: -Offers a compendium of the diverse range of chemical regulations in the countries of the Middle East -Untangles the complex system of permits and licenses that are unique to the various countries in the Middle East -Contains information based on the research and experience of a noted expert in the field -Includes a review of the key regulatory agencies and chemical substance regulations of the Arab States of the Gulf Written for chemical organisations and professionals doing business in the Middle East, Chemical Regulation in the Middle East offers a must-have resource that details the unique chemical regulations in each country in the region.